FRAÇÕES OXIDÁVEIS DO CARBONO EM SOLOS ANTRÓPICOS DO PANTANAL SUL – MATOGROSSENSE - NUNES, Geisielly Pereira; SCHIAVO, Jolimar Antonio; VIANA, Eloise Mello; LARANJEIRA, Laís Thomaz; LIMA, Miriam (ANAIS DO ENIC, 2017)
-